Meningkatkan Hasil Belajar PAK Materi Diriku Melalui Discovery Learning Bagi Siswa Kelas I SDN 11 Sanggau - Blasius Bagung (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2023)
At the beginning of school year, researcher always face the same classic problem in carrying out learning., especially for grade 1 elementary school students. The problem in question is the lack of independence of students in participating in learning and also the lack of student learning results. This case motivates the researchers to find the right solution. One of the solutions that reseachers use is to apply the Discovery Learning model. The selection of this lerning model is based on the syntaxs which places the students as the learning centers and the subject which facilitated by the teacher, try to find their own knowledge with the scientific steps, such as getting stimulation, problem statement, data collecting, data processing, verrification, and generalization. In addition, there are many previous researches have shown that by applying the Discovery Learning model, there is an increase in both learning activities and student learning results. Those are some the reasons that made the researcher decide to conduct this research with the title Improving Learning Results on “Myself” material in Catholic Religion Education with Discovery Learning Model for Grade 1 Students at SDN 11 Sanggau.